GONIOTHALAMUS TRIPETALUS (LAM.) VELDK. & R. M. K. SAUNDERS (ANNONACEAE), COMB. NOV. - J. F. VELDKAMP; R. M. K. SAUNDERS (Reinwardtia, 2010)
J. F. VELDKAMP & R. M. K. SAUNDERS. 2010. Goniothalamus tripetalus (Lam.) Veldk. & R.M.K. Saunders (Annonaceae), comb. nov. Reinwardtia 13(2): 167-169. - Goniothalamus tripetalus (Lam.) Veldk. & R.M.K. Saunders (Annonaceae) dikemukakan sebagai kombinasi baru.